Ossifying Fibroma of Mandible - A Case Report - Gargi Jadaun; A. Bhagwandas Rai; Saeeda Kharodia; Viral Gadhiya (Indian Journal of Dental Research)
Introduction: Ossifying fibromas are rare, non-aggressive benign tumours of the bone, commonly involving the posterior mandible in middle-aged individuals with a female predilection. Findings: Clinical manifestations include asymptomatic expansion of the mandible with infrequent maxillary lesions, pain, malocclusion, and compromised quality of life including aesthetic perception. Owing to multiplicity of features, tendency of recurrence, and possibility of malignant transformation, the diagnosis, treatment, and post-operative management of ossifying fibroma are always a challenge. Take-away Lessons: Study aims to report a clinical case of extensive swelling involving the coronoid process and condyle on the right side to crossing the mid-line of the mandible with compromised functions and aesthetics. The article describes the clinical, histopathological, and radiological features of the case. The possible treatment and challenges encountered are discussed.